2017
DOI: 10.5937/fmet1701089p
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of glass fiber aluminium reinforced riveted joints

Abstract: The airframe of any flying vehicle comprises structural members such as stringers and stiffeners made of sheet metal members, joined by riveted lap joints. Although different joining techniques exist, the rivet type of fastening still stands efficient. Numerous such rivets are required to join the skin completely. The mechanical loading due to the pressurization and depressurization of the fuselage, which occurs once in every flight and the air loads during the cruising flight causes the concentrated stress at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…39 On the other hand, the airframe of any flying vehicle comprises structural members that join by riveted lap joints. 40 It can be said that during riveting process, the structural members are subjected to punch loading. Since the incorporation of GNPs had a positive influence on the behavior of FML panels under punching test, it is recommended to add the GNPs into the composite laminate of FML.…”
Section: Resultsmentioning
confidence: 99%
“…39 On the other hand, the airframe of any flying vehicle comprises structural members that join by riveted lap joints. 40 It can be said that during riveting process, the structural members are subjected to punch loading. Since the incorporation of GNPs had a positive influence on the behavior of FML panels under punching test, it is recommended to add the GNPs into the composite laminate of FML.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have reported on the mechanical properties of FMLs. [ 18–24 ] On contrary, the works related to the mechanical properties of FMLs with nanofillers is very limited. Zhang et al [ 25 ] investigated the influence of multi‐walled carbon nanotubes (MWCNTs) on the flexural and impact performance of GLARE with 3/2 configuration.…”
Section: Introductionmentioning
confidence: 99%